Using a meta-model to build a connection service in an object oriented medical application development environment. - Jean, F. C. (American Medical Informatics Association, 1994)
Interoperability is a key issue in distributed health information systems. This paper presents the design and implementation of the Connection Service (CS) component of the HELIOS medical software engineering environment. An exchange message meta-model based on CEN TC251 recommendations and a message description language are proposed. Using this meta-model, the CS is able either to interpret messages expressed in a given syntax (e.g., EDIFACT, ASTM) and map them to the application objects or to automate the translation of the messages in another syntax. It is concluded that this meta-model approach contributes to the management of semantic heterogeneity.